Corrections to “Effect of Material Changes on the Total Harmonic Distortions Caused by Aluminum Electrolytic Capacitors” - Rene Kalbitz (IEEE Access)
Presents corrections to the paper, (Corrections to “Effect of Material Changes on the Total Harmonic Distortions Caused by Aluminum Electrolytic Capacitors”).